A correlation between self concept and procrastination based on gender in neuroscience perspective - Yussa Annisa Syabilla; Ade Suryanda; Diana Vivanti Sigit (Biosfer: Jurnal Pendidikan Biologi, 2018)
One of the responsibilities of students is to work on academic tasks in a disciplined manner. The problem that arises is when students have a tendency to delay their academic assignments. This is called academic procrastination. Academic procrastination is procrastinating behavior in carrying out academic assignments. One of the internal factors that is important to study related to procrastination is academic self-concept. Self-concept becomes a personality style that is important to be explored further in research on procrastination because a person tends to act in line with the self-concept possessed. There have been many studies conducted related to procrastination. Internal factors of academic procrastination aside from psychological factors also have physiological factors such as neuro activity. This research was conducted at SMAN 44 Jakarta in April-May 2018. The research method used was quantitative descriptive method. The sample used is 120 XI MIPA students. Based on the calculation results obtained normal and homogeneous distributed data. The result of hypothesis testing shows that academic self concept has negative correlation with academic procrastination and rxy is -0473. The academic self concept has a contribution of 22.4% in determining the academic procrastination of learners on Biology subjects. This research implies that the importance of improving students 'academic self-concept, especially for teachers, is expected to be able to do Biology learning with methods that can develop students' academic self-concept.